Nanowire Array Structures for Photocatalytic Energy Conversion and Utilization: A Review of Design Concepts, Assembly and Integration, and Function Enabling. Issue 23 (11th August 2016) - Hoang, Son; Gao, Pu‐Xian
Abstract : The increasing human demand for clean and renewable energy and a cleaner environment has stimulated various materials related research and development for efficient solar energy conversion and utilization, photocatalytic environmental remediation, and photoassisted selective conversion of organic compounds. Among the various candidate solutions to improving the efficiency of these processes, semiconductor nanowire (NW) and nanorod (NR) array structures have been offering a unique tool box combining desirable characteristics in structure, function, and applicability. Efficient photocatalytic energy conversion requires excellent light absorption, readily charge separation, transport, and collection, as well as fast kinetics of interfacial reactions and mass transport of reactants. The long axis of the NW enables adequate light absorption, while the radical axis provides short electron–hole separation distance. Additionally, the NW arrays have relatively high surface area to facilitate interfacial kinetics while their open pore structure allows good mass transport properties. This study reviews the current status of research on NW and NR array structures of some most popular semiconducting materials for photocatalytic energy conversion and utilization including photocatalytic water splitting and CO2 reduction/fixation, dye/quantum dot sensitized solar cells, and other photoassisted reactive applications such as pollutant degradation, selective conversion of organic compounds, and biological disinfection. Abstract : The semiconductor nanowire/nanorod array structures are promising candidates for the practical energy and environmental applications. An overview of recent advances in the applications of the nano‐array structures for the photocatalytic energy conversion and utilization is reviewed with an emphasis on the rational design, assembly and integration, and function enabling of materials and structures.